PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN KARANGTANJUNG PANDEGLANG - Febrianti, Via; Gentari, Ratu Erlina; Syamsudin, Syamsudin (Sains Manajemen, 2017)
This study aims to determine the effect of leadership and work environment to employee performance at the district office karangtanjung Pandeglang, independent variables in thisstudy are leadership and work environment and the dependent variable is the performance of employees.The study used qualitative and quantitative methods with descriptive research explansi level, associative ie for influence between the variables, the source data is primary data and secondary data in the form of a questionnaire. The study population of 33 people, and 33 samples were taken, and analyzed with SPSS version 20:00 Based on the results of this study concluded that 1) there is positive and significant correlation between leadership on employee performance, 2) there is no effect and no significant between work environment to employee performance, 3) there are significant positive and significant correlation between leadership and work environment to employee performance